PENGUATAN MATERI LINGKUNGAN HIDUP DAN PENGOLAHAN SAMPAH ORGANIK DI SMA YAPIS NIMBOKRANG, JAYAPURA - Suharno Suharno; Rosye H.R. Tanjung; Efray Wanimbo (JURNAL PENGABDIAN PAPUA, 2021)
The aims of this activity were to empower local community to turn organic waste into eco-enzyme. The community was SMA Yapis Nimbokrang, Jayapura. The method use were presentation and practice. After practicing, the student of SMA Yapis were tested to evaluate their understanding regarding eco-enzyme. The result shown that their understanding rose from 32% to 98.4 %. The knowledge regarding compos, adn biogas rose to 100% and 44% respectively. For eco-enzyme, student knowledge rose to 85% from 14 %. Therefore, we can conclude that this activity has positive impact in raising people knowledge and awarness in terms of processing organic waste sustainably. Keywords: local community; eco-enzyme; compos; Nimbokrang; Jayapura